The effect of design parameters on mechanical characteristics of porous CoCrMo scaffold manufactured by additive manufacturing - Siti Rohaida, Mohamed; Saiful Anwar, Che Ghani; Sawangsri, Worapoong; Mohd Azwan, Azizi (Universiti Tun Hussein Onn Malaysia Publisher, 2021)
Metallic orthopedic implants to replace or generate lost bones caused by traumatic road traffic injuries often failed prematurely after surgery. Bone resorption caused by stress shielding of metallic implants became a main concern as it can potentially lead to bone implant failure. Metallic scaffold designed in porous structures fabricated using additive manufacturing (AM) are widely used as bone implant, since the elastic modulus of the scaffolds can easily tailored according to the bone properties, and the large surfaces are beneficial to cell in-growth. The microarchitecture of scaffold can control their mechanical and biological properties, but it is found that there is lack of systematic approach to select a cell topology with full perspective requirements of bone implant. This paper presents a systematic approach of design space mapping for two CoCrMo unit cell shapes namely square and diamond to understand the relationship between geometrical parameters with additive manufacturing limitation, mechanical and bone ingrowth requirements. The compressive response of the components was simulated by finite element analysis and the influence of design parameters on the scaffold behaviour was compared theoretically with Gibson and Ashby model. The FEA give prediction for effective elastic modulus of 3 GPa to 4.8 GPa for diamond type and range of 6 GPa to 29 GPa for square type. Experimental results showed accurate prediction of compression elastic modulus with average error of 13% for diamond type and 35% for square type respectively. The significance of the methodology and the results showed that different design parameters of the structures can play a major role in the mechanical behaviour of the metallic scaffold.